2022
DOI: 10.1111/jonm.13599
|View full text |Cite
|
Sign up to set email alerts
|

Work environment and mental health in nurse assistants, nurses and health executives: Results from the AMADEUS study

Abstract: Aim This study aimed to explore work environment and mental health in nurse assistants, nurses and health executives in a national large‐scale study. Background We have data for physicians but not for other health care workers categories. Methods A total of 6935 participants were recruited between May and June 2021 by professional mailings and professional networks. Results All professional categories reported high rates of high psychological demand (>90%), low social support (>60%), burnout (50% to 60%), expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Strategies to prevent bullying in the workplace and increase healthy lifestyle choices were paramount to the prevention of moral stressors and PMIEs. 55…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies to prevent bullying in the workplace and increase healthy lifestyle choices were paramount to the prevention of moral stressors and PMIEs. 55…”
Section: Discussionmentioning
confidence: 99%
“…54 Healthcare institutions must acknowledge the value of healthcare workers, empower them, and increase their autonomy. Lucas et al 55 suggested nursing managers develop interventions to reduce psychological demand and increase the recognition of individual accomplishments and social support among colleagues. Strategies to prevent bullying in the workplace and increase healthy lifestyle choices were paramount to the prevention of moral stressors and PMIEs.…”
Section: Addressing the Work Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the well-being, including burnout, of nursing staff, were also conducted during the COVID-19 pandemic period. Burnout incidence rates were as high as 60% of study participants 13 . A study of emergency department staff showed higher rates (43%) of burnout in nursing staff compared to other participating healthcare professionals.…”
Section: Introductionmentioning
confidence: 90%
“…These studies have revealed that heavy workloads, time pressure, contradictory demands, conflicts of value associated with low rewards, and lack of resources influence people's experience and expectations at work. 17 Lack of recognition from superiors and peers is often associated with psychological distress and turnover. 18 Other studies have highlighted the interpenetration of personal life goals and decisions around leaving one's job.…”
Section: Problematising the Crisis: Agency And Meaning At Workmentioning
confidence: 99%